2017
DOI: 10.18632/oncotarget.19563
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience of afatinib as a first-line therapy for advanced EGFR mutation-positive lung adenocarcinoma

Abstract: We evaluated the real-world efficacy and side effects of afatinib as a first-line therapy for advanced EGFR mutation-positive lung adenocarcinoma. The medical records of patients receiving afatinib as a first-line therapy after National Health Insurance reimbursement between May 2014 and January 2016 were reviewed, and information on patient characteristics and treatment courses were collected consecutively. Rebiopsy tissue was collected for EGFR mutation and MET amplification analyses. MET amplification was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
61
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 39 publications
16
61
3
Order By: Relevance
“…A previous real world study indicated that a starting afatinib dose of 30 mg daily achieved similar PFS to 40 mg daily, but led to fewer serious adverse events . Our results support this conclusion.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A previous real world study indicated that a starting afatinib dose of 30 mg daily achieved similar PFS to 40 mg daily, but led to fewer serious adverse events . Our results support this conclusion.…”
Section: Discussionsupporting
confidence: 88%
“…22 One real world study indicated that a starting afatinib dose of 30mg daily had similar PFS to 40mg daily, but led to fewer serious adverse events. 21 Our research also supported this conclusion. In this study, there were no significant differences in various characteristics and median PFS between these two dose groups.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The median time to progression (TTP) in all patients was 20.8 months and the median TTP in those who commenced at a dose of ≤ 30 mg of afatinib was 25.9 months. In a real‐world cohort study in Taiwan, there was no significant difference in median PFS in the first six months between the 40 mg and < 40 mg groups (12.0 vs. 11.0 months, respectively) . In a retrospective analysis of the efficacy of 40 mg versus dose reduction to < 40 mg of afatinib, there were no significant differences between the groups in the median time to treatment failure (405 vs. 472 days, respectively; P = 0.2271) .…”
Section: Discussionmentioning
confidence: 93%